2005
DOI: 10.1016/j.crvi.2005.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Has the kouprey (Bos sauveli Urbain, 1937) been domesticated in Cambodia?

Abstract: The kouprey (Bos sauveli Urbain, 1937) is a very rare bovid species of Cambodia, which may be extinct in the wild, as no living specimen has been observed for a long time. Here, we describe a complete taxidermy mount, which presents astonishing morphological similarities with the kouprey. The animal was mounted in 1871 at the National Museum of Natural History in Paris, where it was referenced as No. 1871-576. It was deposited at the Natural History Museum of Bourges, France, in 1931, where it is still conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
(35 reference statements)
2
16
0
Order By: Relevance
“…Genetic distance and relatively high values of bootstrapping and Bayesian posterior probability supported the distinction of these two domestic species. These findings are identical to some earlier reports based on sequences of mtDNA of cattle species (Hassanin and Ropiquet, 2004;Verkaar et al, 2004;Hassanin et al, 2006;Ma et al, 2007). Bradley et al (1996) concluded that the association of taurine and zebu cattle reflects the fertility of female as well male hybrid offspring, with a divergence time of 100,000 to 200,000 years.…”
Section: Genetic Distancesupporting
confidence: 79%
See 1 more Smart Citation
“…Genetic distance and relatively high values of bootstrapping and Bayesian posterior probability supported the distinction of these two domestic species. These findings are identical to some earlier reports based on sequences of mtDNA of cattle species (Hassanin and Ropiquet, 2004;Verkaar et al, 2004;Hassanin et al, 2006;Ma et al, 2007). Bradley et al (1996) concluded that the association of taurine and zebu cattle reflects the fertility of female as well male hybrid offspring, with a divergence time of 100,000 to 200,000 years.…”
Section: Genetic Distancesupporting
confidence: 79%
“…Phylogenetically, gaurs belong to the tribe Bovini and are further assigned to the subtribe Bovina, which includes some other extant species such as B. taurus (taurine cattle), B. indicus (zebu cattle), B. javanicus (banteng), B. grunniens (yak), Bison bison (American bison), Bison bonasus (European bison), and other Bubalus species (Hassanin and Ropiquet, 2004;Hassanin et al, 2006). To date, studies on the relationship of species in the genus Bos have been investigated by researchers around the world using several types of molecular data and techniques: a) mitochondrial DNA (mtDNA) sequence data (Matthee and Davis, 2001;Cai et al, 2007;Gu et al, 2007;Ginja et al, 2010); b) nuclear DNA sequence data and microsatellites (Kikkawa et al, 2003;MacEachern et al, 2009), and c) DNA fingerprinting and amplified fragment length polymorphism (AFLP) techniques (Vasil'ev et al, 2002;Buntjer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis, and the fact that mtDNA is maternally inherited, implies that the mtDNA of banteng was transferred into the kouprey ancestor through a mating between a zebu male and a banteng female during historic times. This scenario is apparently plausible, as Cyb sequences related to the kouprey have already been detected in domestic cattle from Cambodia (specimen from Bourges; Hassanin et al , 2006), and as banteng maternal introgression has been previously evidenced in Indonesian zebu (Kikkawa et al , 2003; Nijman et al , 2003). In Java, it is generally accepted that the Bali cattle was domesticated from wild banteng (Martojo, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Several of these signatures were previously found in two Cyb fragments produced for a specimen preserved in the collections of the Natural History Museum of Bourges (No. 1871‐576, MNHN; Hassanin et al , 2006). The first Cyb fragment (positions 163–405, accession number DQ275470) is perfectly identical to the kouprey, but differs from Cambodian banteng at positions 273 (C) and 396 (A).…”
Section: Resultsmentioning
confidence: 99%
“…Coupled with phylogenetic analyses, we observed that the fragment between positions 867 and 1,140 of the cyt b gene contains species-specific diagnostic sites, which allowed us to distinguish the four species unambiguously. DNA amplification of this 274 base pair (bp) sequence was performed using the following primers: L15612: 5 0 -CGATCAATYCCYAAYAAACTAGG-3 0 and H15915 (reverse): -TCTCCATTTCTGGTTTACAAGAC-3 0 [Hassanin et al, 2006]. The cyt b PCRs on fecal DNA were run under the following conditions: 1 Â PCR buffer (10 mM Tris-HCl, pH 8.3, 50 mM KCl, 2 mM MgCl2), 0.2 mM of each dNTP, 1 mM of each primer, 0.5 units of AmpliTaq Gold TM (Applied Biosystems, Warrington, UK) and 5 mL of fecal DNA in a final reaction volume of 25 mL.…”
Section: Species Assessment Of the Samples Collected In The Fieldmentioning
confidence: 99%